Environmental Innovation and Sustainability in Remanufacturing: A Strategic Review - Altaf, Aramish; Shahzad, Salman (Journal of Policy Options, 2021)
The aim of this article is to present a concise review of the relationship between environmental sustainability, environmental innovation, and remanufacturing. Traditionally, the corporate environment was understood to shape firm performance based on economic, social, political, and technological factors. However, with growing global awareness of environmental concerns, sustainability and innovation in environmental practices, such as remanufacturing, have emerged as critical determinants of long-term business success. Environmental sustainability involves minimizing negative impacts on the environment while maintaining economic growth, and environmental innovation refers to new practices and technologies aimed at reducing ecological footprints. Remanufacturing, a process that restores used products to a "like-new" condition, is increasingly seen as a key strategy for achieving both sustainability and innovation, helping companies reduce waste and resource consumption. Understanding the interconnections between these concepts is vital for businesses seeking to enhance their environmental performance and meet growing demands for sustainable practices. However, in recent years, environmental factors have also become integral to the corporate environment. This shift reflects the growing recognition that businesses must consider their environmental impact alongside traditional economic and social factors. Recent research has increasingly focused on the environmental management system, which has proven to be a highly effective tool for organizations aiming to improve their environmental performance. Environmental management system helps businesses systematically manage their environmental responsibilities and ensures compliance with regulations while promoting sustainability. In addition to environmental management system, there has been a strong emphasis on environmental innovation, particularly in the areas of technological product and process innovation. Environmental innovation refers to the development and implementation of new technologies and processes that reduce environmental harm, enhance resource efficiency, and support sustainable production. These innovations enable firms to reduce waste, lower emissions, and use materials more efficiently, contributing to both environmental sustainability and improved competitiveness. By incorporating environmental factors into corporate strategy and focusing on innovation, businesses can better address the challenges of sustainability in a rapidly changing global landscape. Product innovation has been extensively researched in fields such as new product development, design for the environment, and design for remanufacturing. Studies on remanufacturing demonstrate that it can be both profitable and environmentally beneficial, as it reduces waste, conserves resources, and lowers emissions. However, there is a noticeable gap in the literature regarding process innovation, particularly in remanufacturing. While product innovation has been widely explored, the lack of attention to process innovation leaves room for further exploration. Process innovation in remanufacturing refers to improvements in the methods and technologies used to refurbish products, which can enhance efficiency and sustainability. Technological advancements in both product and process innovation play a crucial role in reducing environmental impacts by promoting cleaner, more resource-efficient practices. Therefore, there is an emerging need for more in-depth studies on process innovation, specifically in remanufacturing, to fully realize its potential in contributing to environmental sustainability and economic viability.